Banking Models Under the Impact of the Post-Crisis Organizational Changes Apt to Confer Sustainable Financial Stability - Romanian Experience - Claudia Gabriela Baicu; Olimpia State (Amfiteatru Economic)
The global financial crisis led to substantial changes in the operating environment of banks. Reforming the regulatory framework of financial and banking activity and the increase role of state in banking systems in many countries are important factors that involve major changes in the organizing of banking activity, the strategies adopted, the business models practiced, etc. Based on these considerations, the paper examines trends in banking models after the 2007 crisis. The analysis of the banking models is performed from the perspective of the deep organizational changes that affected the banking environment and sustainable financial stability. The study focuses on the analysis of the banking sustenability and the business model in the Romanian banking system, in the context of the post-crisis organizational changes. The profound interdependence of the Romanian banking system with the banking systems of the European countries and the international tendencies in financial regulation are important factors that influence the business models of the Romanian banks. The banking model practiced in Romania continues to be the traditional one. Currently, the most important challenges of the Romanian banking system are the growth of the non-performing loans, the loans in foreign currency to unhedged borrowers, the pressure to meet the Basel III requirements, as well as the possibility that the exposure of foreign banks towards Romania to decrease.